Endobronchial Lesions Caused by Nontuberculous Mycobacteria in Apparently Healthy Pediatric Patients. Issue 5 (May 2015) - Kröner, Carolin; Griese, Matthias; Kappler, Matthias; Schoen, Carola; Hoffmann, Florian; Nicolai, Thomas; Reiter, Karl
<x xml:space="preserve">Abstract</x> Pulmonary disease caused by nontuberculous mycobacteria in healthy children is rare, and its pathogenesis is unknown in most cases and standardized treatment is lacking. Here, we report various endobronchial manifestations in 5 patients including hitherto undescribed diffuse tracheobronchial granulomas in 2 patients. Bronchoscopic debulking was performed in all patients and tuberculostatic treatment in 4. All patients including 1 without tuberculostatic treatment showed remission.